Examining social support and procrastination among college students - Miller, Ashley; Bravo, Diamond; Arnold, Elisha; Rincon, Brenda; Murray, Carolyn (Frontiers in Psychology, 2024)
The current study investigated how social support may mitigate the risk of procrastination, particularly among those high in intolerance of uncertainty. This study examined associations between personality traits, procrastination, and perceived social support among 394 undergraduate students. Participants completed self-reported measures of intolerance of uncertainty, procrastination, and social support from family, friends, and significant others. Regression analyses revealed a significant interaction between family social support and intolerance of uncertainty in predicting procrastination. Study findings have implications for understanding how familial support resources may reduce risks for procrastination in college students.